2016
DOI: 10.1103/physrevb.93.085104
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous frequency and temperature-dependent scattering and Hund's coupling in the almost quantum critical heavy-fermion systemCeFe2Ge2

Abstract: We present THz range optical conductivity data of a thin film of the near quantum critical heavy fermion compound CeFe2Ge2. Our complex conductivity measurements find a deviation from conventional Drude-like transport in a temperature range previously reported to exhibit unconventional behavior. We calculate the frequency dependent effective mass and scattering rate using an extended Drude model analysis. We find the inelastic scattering rate can be described by a temperature dependent power-law ω n(T ) where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…From the extended Drude analysis, it is clear that the behavior of the scattering rate and effective mass indicate that the crossover into the FL regime is not particularly sharp. Unlike other heavy-fermion compounds which can show a dramatic increase in the effective mass [8,22], the weaker mass enhancement of quasiparticles and the slow crossover as a function of temperature has been pro- posed to originate from the mixed-valence states of Yb [11]. The two important energy scales in this material are set by the FL coherence temperature T * = 40 K and the Kondo temperature T K = 670K.…”
Section: Discussionmentioning
confidence: 99%
“…From the extended Drude analysis, it is clear that the behavior of the scattering rate and effective mass indicate that the crossover into the FL regime is not particularly sharp. Unlike other heavy-fermion compounds which can show a dramatic increase in the effective mass [8,22], the weaker mass enhancement of quasiparticles and the slow crossover as a function of temperature has been pro- posed to originate from the mixed-valence states of Yb [11]. The two important energy scales in this material are set by the FL coherence temperature T * = 40 K and the Kondo temperature T K = 670K.…”
Section: Discussionmentioning
confidence: 99%
“…For temperatures below 12 K, the frequency dependence of the relaxation rate could be modeled as 1/τ (ωT) = 1/τ (0T) + Aω n . It was found that the exponent n decreases from ≈2 to ≈1 at temperatures below 3 K. The observed behavior was explained as manifestation of non-Fermi liquid behavior due to proximity to a QCP [214], which is also supported by the dc resistivity measurement in this compound that shows ≈T 1.5 dependence between 1.5 and 10 K [86]. However, the discrepancy in the observed exponents between the optical and dc conductivity measurements could not be explained within the existing theoretical models [231].…”
Section: Time-domain Thz Spectroscopymentioning
confidence: 93%
“…which can be directly measured in optical conductivity measurements [207,214]. In strongly interacting systems, a renormalized plasma frequency can be defined as (ω * p ) 2 = 4πNe 2 m * that captures the spectral weight of only the renormalized band, where (…”
Section: Optical Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In particular time-domain terahertz spectroscopy has been proven very useful in studying different material systems at low temperatures including superconductors, 14,15 quantum magnets, [16][17][18][19] exciton states in TiO 2 nanotubes, 20 and topological insulators. 13,[21][22][23] With the photoconductive switches method of TDTS, one typically splits an infrared femtosecond laser pulse along two paths and sequentially excites a pair of photoconductive "Auston"-switch antennae.…”
Section: Introductionmentioning
confidence: 99%